Aggressiveness Overcomes Body-Size Effects in Fights Staged between Invasive and Native Fish Species with Overlapping Niches - Carretero Sanches, Fabio Henrique [UNESP]; Miyai, Caio Akira [UNESP]; Costa, Tânia Marcia [UNESP]; Christofoletti, Ronaldo Adriano; Volpato, Gilson Luiz [UNESP]; Barreto, Rodrigo Egydio [UNESP] (Public Library Science, 2012)
Approximately 50 years ago, Nile tilapia were accidentally introduced to Brazil, and the decline of pearl cichlid populations, which has been intensified by habitat degradation, in some locations has been associated with the presence of Nile tilapia. There is, however, little strong empirical evidence for the negative interaction of non-native fish populations with native fish populations; such evidence would indicate a potential behavioural mechanism that could cause the population of the native fish to decline. In this study, we show that in fights staged between pairs of Nile tilapia and pearl cichlids of differing body size, the Nile tilapia were more aggressive than the pearl cichlid. Because this effect prevailed over body-size effects, the pearl cichlids were at a disadvantage. The niche overlap between the Nile tilapia and the pearl cichlid in nature, and the competitive advantage shown by the Nile tilapia in this study potentially represent one of several possible results of the negative interactions imposed by an invasive species. These negative effects may reduce population viability of the native species and cause competitive exclusion.